2015
DOI: 10.1097/bpo.0000000000000267
|View full text |Cite
|
Sign up to set email alerts
|

Pinless Halo in the Pediatric Population

Abstract: Level IV-Case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…While most halo complications involve pin site loosening or infection, the use of pinless halos also has significant complication rates. Bakshi et al 14 reported a 21% complication rate using a pinless halo in the pediatric population. Other rare complications of halo use have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…While most halo complications involve pin site loosening or infection, the use of pinless halos also has significant complication rates. Bakshi et al 14 reported a 21% complication rate using a pinless halo in the pediatric population. Other rare complications of halo use have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…We identified seven publications presenting conservative treatment with HF in patients with traumatic AARS. The results and success rates are presented in Table 2 [ 6 , 11 , 17 , 29 , 35 , 44 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The conventional halo can be associated with significant adverse events: infection, pin loosening, dysphagia, dural/ skull penetration, and pressure ulcers. [ 5 ] A pinless halo avoids many of these problems at the perceived expense of the stability which the pins ensure. Indeed, noninvasive halos are applied widely in pediatric neurosurgery for immobilization in situations such as congenital muscular torticollis, conservative management of nontraumatic atlantoaxial rotary subluxation, post cervical fusion surgery, and stable occipital condyle fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, noninvasive halos are applied widely in pediatric neurosurgery for immobilization in situations such as congenital muscular torticollis, conservative management of nontraumatic atlantoaxial rotary subluxation, post cervical fusion surgery, and stable occipital condyle fractures. [ 5 ] Pinless halo use can lead to occipital pressure ulcers and skin infection. Our patient had an occipital laceration from the original trauma and this developed into a pressure ulcer, which needed debridement and a course of antibiotics.…”
Section: Discussionmentioning
confidence: 99%